Impact of Telecommunication on Transportation System of Dhaka City (Journal of Bangladesh Institute of Planners, 2013)
Dhaka city, being one of the most densely populated cities of the world, is suffering tremendous problems especially in transport sector. Also, with the increase in level of urbanization the situation is becoming more acute in the unbearable traffic congestion which takes away around 3.2 million work-hours in a year. Telecommunication is another way of communicating besides physical transportation and now-a-days a large number of travel demands can be satisfied through this advancing technology. In Dhaka, both these modes of communication have experienced tremendous growth over the past few decades and since they can serve the same demands to some extent, it is implied that development in one sector may potentially mitigate the problems of other. In this context, this study investigates the impact of telecommunication on transportation system of Dhaka city. From the impact analysis, it has been found that transportation demand has a positive or complementarity relationship with telecommunication demand and transportation cost. Also, telecommunication demand and supply has positive relationship with transport cost in Dhaka city. Socio-demographic conditions tend to reduce transportation cost and increase telecommunication cost. The implication of the effect of land use change is that non-residential use of land contributes towards the increase of both the supply and demand of telecommunications and travel. It is also suggested by the findings that proper integration transport and telecommunication sector is necessary for this city in order to use telecommunication as a substitute of transport sector to improve the mobility of the city dwellers.Vol. 6, December 2013, pp. 125-135